Comprehensive study of thermal degradation behavior of carbon fiber flexible sucker rods: Product characteristics, kinetics and thermodynamics. (1st February 2023) - Guan, Wenhan; Han, Zhaohui; Su, Wenting; Guo, Shenghui; Guo, Yongjing
Highlights: Pyrolysis behavior of CFSR was studied using TG-FTIR and GC–MS. The elemental, proximate, and compositional analyses of CFSR was measured. Pyrolysis kinetics were studied using model-free and model-fitting methods. Abstract: Carbon fiber flexible sucker rods (CFSR) are important as an essential component of oilfield extraction and their potential energy resource after decommissioning is very important. This research presents a detailed examination of the pyrolysis kinetic triplets and product characterization of CFSR that used a thermogravimetric analyzer (TGA), thermogravimetric-Fourier transform infrared spectroscopy (TG-FTIR) and gas chromatograph-mass spectrometer (GC-MS). The results revealed that the CFSR reaction interval was between 240 and 550 °C. Model fitting and the Criado method were used to determine the reaction control mechanism, and the average activation energies obtained by four model-free methods were 201.52(FWO), 201.93(KAS), 217.96(FM), and 202.29(Starink) kJ/mol. The byproducts consist mainly of acids, aromatics and hydrocarbons. In addition, the regenerated carbon fibers have a smooth surface and almost no residual resin as the temperature climbs to 600 °C. The results of the study facilitate the process optimization of carbon fiber composites and provide theoretical guidance and data support for subsequent development and utilization. The results of the study facilitate the process optimization of carbon fiber composites and provide theoretical guidance and data support for subsequent development and utilization.